Parameters of physical performance and physical effort required in the different playing positions in the soccer - Altavilla, G.; Riela, L.; Raiola, G. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: The purpose of this study is to examine, with respect to their playing position, the effort physical required at footballers during the match, the relationship between the metabolic power and the resistance capacity (total distance covered). Methods: The study method is experimental with the division of the sample in 3 groups of 10 players, divided by role (Attackers n = 10. Midfielders n = 10 and Defenders n = 10). The physical effort required, metabolic activity profiles and endurance capacity were collected on (30) elite senior male Italian football players using global positioning system. Data were collected during (20) friendly matches. Analysis of statistical data has been conducted with Anova to check the differences between the three groups of footballers: while has been used Person's correlation to compare the metabolic power with resistance capacity (total distance covered). The significant differences has been fixed in p<0.05. Results: For all match-related parameters, physical performance was higher for defenders and midfielders compared to attackers. Correlations were observed between metabolic power and total covered distance in the different roles of play. Conclusions: The physical effort demands during a football game differ by game position as well as the correlation between the metabolic potency and the distance covered in the different play positions has been confirmed.